Effects of Limit Feeding and Shade Allocation on Growing Calf Performance, Water Usage, and Animal Comfort - Z. L. DeBord; Z. M. Duncan; M. G. Pflughoeft; K. J. Suhr; W. C. Ellis; W. R. Hollenbeck; S. P. Montgomery; T. J. Spore; E. C. Titgemeyer; D. A. Blasi; A. J. Tarpoff (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to evaluate the impact of limit feeding in conjunction withshade allotment on animal performance, animal comfort, and water usage during periods of heat stress. Study Description:During the summers of 2021 and 2022, 852 heifers were assigned to one of four treatments: limit-fed high-energy ration or high-roughage ration fed forad libitumintake with or without access to shade. Growth performance and water usage were measured during a 90-day growing period. Calves were fed a gut equilibration diet for 7 days to account for gut fill. The Bottom Line:Limit feeding a high-energy ration at 2.2% of body weight daily on a dry matter basis in combination with shade can improve animal efficiency, reduce water consumption, and improve animal comfort during periods of heat stress.
Keywords: growing cattle; heat stress; limit feeding; shade